Effectiveness of Canakinumab Treatment in Colchicine Resistant Familial Mediterranean Fever Cases - Yücel, Burcu Bozkaya; Aydog, Ozlem; Nalcacioglu, Hulya; Yılmaz, Ayşegül (Frontiers in Pediatrics, 2021)
Anti-interleukin 1 agents are used successfully in colchicine-resistant or intolerant Familial Mediterranean Fever (FMF) patients. Sixty-five patients with FMF who received canakinumab treatment for at least 6 months due to colchicine resistance or intolerance between 2016 and 2020 in our department were retrospectively analyzed. Canakinumab treatment was given subcutaneously every 4 weeks. After completing monthly canakinumab therapy over 12 months, in patients with complete remission, the dosing interval was extended to every 1.5 months for 6 months, then every 2 months for 6 months, and finally every 3 months for a year. In patients without disease activation, canakinumab treatment was discontinued at the end of 3 years and followed up with colchicine treatment. Patients who had a flare switched to the previous dosing interval. In patients with renal amyloidosis, monthly canakinumab treatment was continued without extending the dose intervals. The mean duration of canakinumab use in our patients was 31.4 ± 10.57 months (6–52 months). The mean age at onset of symptoms was 4.65 ± 3.84 (range, 1–18) years, and the mean age at diagnosis was 5.59 ± 3.9 (range, 4–19) years. Complete remission was achieved in 57 (87.6%) and partial remission in seven (10.7%) patients. One patient was unresponsive to treatment. Canakinumab treatment was discontinued in three patients with complete remission and one patient with drug resistance. Erythrocyte sedimentation rate (ESR) (51.85 ± 15.7 vs. 27.80 ± 13.73 mm/h) and C-reactive protein (CRP) [26 (3-73) vs. 5 (1–48) mg/L] values were compared before and after canakinumab treatment in attack-free periods, a significant decrease was found after canakinumab treatment (p < 0.001, p < 0.001, respectively). Bodyweight Z-scores (respectively −0.80 ± 0.86 vs. −0.49 ± 0.92) were compared, similarly, a statistically significant increase after canakinumab treatment (p < 0.001), but no significant increase in height Z scores (−1.00 ± 0.88 vs. −0.96 ± 0.94) (p = 0.445) was detected. Four patients had FMF-related renal amyloidosis. The decrease in proteinuria with canakinumab treatment was not statistically significant (p = 0.068). Cervical lymphadenitis developed in one and local reactions in two patients. No severe adverse effects requiring discontinuation of canakinumab treatment were observed. Our study showed that canakinumab treatment was highly effective, well-tolerated in pediatric FMF patients, and controlled extension of the canakinumab dose interval was safe.